Weather Analysis and Forecasting : applying satellite water vapor imagery and potential vorticity analysis - Santurette, Patrick; Georgiev, Christo (Academic Press, 2005)
Weather Analysis and Forecasting: Applying Satellite Water Vapor Imagery and Potential Vorticity Analysis, Second Edition, is a step-by-step essential training manual for forecasters in meteorological services worldwide, and a valuable text for graduate students in atmospheric physics and satellite meteorology. In this practical guide, P. Santurette, C.G. Georgiev, and K. Maynard show how to interpret water vapor patterns in terms of dynamical processes in the atmosphere and their relation to diagnostics available from numerical weather prediction models. In particular, they concentrate on the close relationship between satellite imagery and the potential vorticity fields in the upper troposphere and lower stratosphere. These applications are illustrated with color images based on real meteorological situations over mid-latitudes, subtropical and tropical areas.
PART I: Fundamentals>1. A dynamical view of synoptic development>2. The interpretation problem of satellite water vapor imagery>>PART II: Practical use of water vapor imagery and dynamical fields>3. Significant water vapor imagery features associated with synoptic dynamical structures>4. Use of water vapor imagery for assessing NWP model behavior and improving forecasts>>Appendices>A. Radiative transfer theory and some radiation effects for the WV channels of Meteosat, GOES, and MSG>B. Synthetic (pseudo) water vapor images>C. PV modification technique and PV inversion to correct the initial state of the numerical model>D. Glossary of acronyms.
Keywords: Satellite meteorology; Water vapor, Atmospheric; Weather forecasting; Satellite meteorology; Water vapor, Atmospheric; Weather forecasting; Electronic books